The Little Data Book on Private Sector Development 2013 - World Bank (Washington, DC, 2013)
Access to reliable cross-country data on private sector development is crucial when formulating responses to economic crises. The data sources presented in this book report on the scope and types of regulations that enhance and constrain business activity and provide information on business owners' assessment of the business environment. The data have led to new research, enabled benchmarking, and informed the reform process in many developing countries. This guide book includes indicators on the economic and social context, the investment climate, private sector investment, finance and banking, and infrastructure. The indicators that are included in this book provide users with a general understanding of the private sector in each country. Indicators displayed in the tables are defined in the glossary, which also lists data sources.